2000
DOI: 10.1074/jbc.275.5.3343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Mitochondrial DNA Copy Number and Cytochromec Oxidase Gene Expression in Rat Skeletal Muscle, Liver, and Heart

Abstract: Mitochondrial DNA (mtDNA) deletions and mutations have been reported to occur with aging in various tissues. To determine the functional impact of these changes, we measured mtDNA copy number, mitochondria-encoded cytochrome c oxidase (COX) subunit I and III transcript levels, and COX enzyme activity in skeletal muscles (medial and lateral gastrocnemius and soleus), liver, and heart in 6-and 27-month-old rats. Substantial age-related reductions of mtDNA copy number occurred in skeletal muscle groups (؊23-40%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
243
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(262 citation statements)
references
References 39 publications
15
243
3
1
Order By: Relevance
“…In addition, our data reporting mtDNA loss with aging in the rat frontal cortex are in agreement with previous reports, such as that by McInerny et al (2009), who described mtDNA decrease in rat cerebral cortex, and with several other reports in various rat tissues such as skeletal muscle and liver (Barazzoni et al 2000) as well as in humans (Short et al 2005).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, our data reporting mtDNA loss with aging in the rat frontal cortex are in agreement with previous reports, such as that by McInerny et al (2009), who described mtDNA decrease in rat cerebral cortex, and with several other reports in various rat tissues such as skeletal muscle and liver (Barazzoni et al 2000) as well as in humans (Short et al 2005).…”
Section: Discussionsupporting
confidence: 83%
“…As a consequence of oxidative stress, mtDNA can undergo quantitative and qualitative alterations (bases modifications, abasic sites, single-and doublestrand breaks, point mutations, and large-sized deletions) that affect its structure and function. Age-related changes in the mtDNA content have often been found in various mammalian tissues (Barazzoni et al 2000;Barrientos et al 1997;Dinardo et al 2003;Lee et al 1998;McInerny et al 2009;Pesce et al 2001Pesce et al , 2005Short et al 2005), as well as in single cells (Blokhin et al 2008). Large-sized deletions are among the most investigated qualitative alterations of mtDNA.…”
mentioning
confidence: 99%
“…[22][23][24][25] For a given chromosomal region, short reads mapped to the region were retrieved from the BAM file at the FTP site of the 1000 Genomes Project 26 using samtools. 27 This was done for the whole mtDNA region and the autosomal regions; the numbers of short reads in the two regions were used to compute mtDNA/nDNA.…”
Section: Estimation Of Mtdna Copy Numbermentioning
confidence: 99%
“…Some laboratories report no attenuation of respiratory complexes with age (Torii et al, 1992;Barazzoni et al, 2000;Kwong & Sohal, 2000), whereas others have observed decreased complex I and IV activities (Sugiyama et al, 1993;Andreu et al, 1998), transcript levels (Andreu et al, 1998;Hudson et al, 1998) and protein synthesis (Hudson et al, 1998). In rat models of congestive heart failure, declines in transcripts for subunits of complex IV and enzyme activity are associated with decreased levels of the nuclear factors PGC-1α, Tfam and NRF-2 (Garnier et al, 2003).…”
Section: (Ii) Heartmentioning
confidence: 99%
“…Respiratory chain complexes in mitotic tissues such as liver and kidney from a variety of species seem not to decline with age (Sugiyama et al, 1993;Barazzoni et al, 2000;Kwong & Sohal, 2000;Navarro et al, 2002). In cell culture both human fibroblasts (Martinez et al, 1991) and rat hepatocytes (Hagen et al, 1997) have been shown to develop distinct populations judged on the basis of membrane potential and replicative ability.…”
Section: (Iv) Proliferating Tissuementioning
confidence: 99%